If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(9*x-1)/2 = 13 // - 13
(9*x-1)/2-13 = 0
(9*x-1)/2+(-13*2)/2 = 0
9*x-13*2-1 = 0
9*x-27 = 0
(9*x-27)/2 = 0
(9*x-27)/2 = 0 // * 2
9*x-27 = 0
9*x-27 = 0 // + 27
9*x = 27 // : 9
x = 27/9
x = 3
x = 3
| 4x-13-6x+4=3-8x-8+2x | | 60=-.16x+68.67 | | 5(-6+3x)=-12 | | (3/7x)-5/x=3 | | -1/3/2 | | 5(-6+3x)=-30 | | 79=kji | | 2-I=-42 | | x/(x+5)=10 | | 5(3x+2)=115 | | 1/7(x+21)=6 | | -7x+10=-3x-22 | | x^3-16x^2+20x+400=0 | | 3x(x)+8x=5x-4x(x) | | 2x+2=-22+5x | | (3w-1/2)=(6w-2/7)+3 | | -56-7x=19+8x | | z=14x+5y | | 7x-4=x+56 | | (11.2)2-(0.375/3) | | ((6t)^2+9)^1/2 | | 5x(x)=10x | | (.0105)(.1417)= | | -243=-90(10+x) | | p=m(1-DT) | | 120=-12(x-5) | | 7(4-x)+9=1+4(x-1) | | x-1+x=-9 | | 2x+6x+8=6x+4 | | 5x-6+3x=-6 | | 5-t-3=-1+2(t-3) | | 4x+7=-8x-29 |